John Ruskin : his life and works - Bailey, Effie Elizabeth (My University, 1900)
Introduction: John Ruskin, the world renowned critic of art, philosopher, and reformer, was born in London, England, February 8, 1819. He was a Scotchman by birth, although his parents lived in England. His father was a successful and wealthy wine-merchant, a lover of nature and art; his mother was a very strict and pious woman, possessing a loving and religious nature; although, at times she was passionate and over indulgent in the ruling of her child, looking upon him as a “sacred trust, never a pleasure or past time.” His surroundings were those of the city life, noted teachers, artists, reformers, and men of letters, all of whom accomplished and contributed something toward the development of English literature. His early training began in the house, with his mother’s teaching, it being one of the marked features and influences in his learning and writing. As a child he had a gentle disposition, and showed traces of fond love of study. The father hoped to see his son poet laureate. His mother’s greatest desire was for him to enter into evangelistic work; but this proposition was not heartily received by young Ruskin, and a copy of Rogers “Italy” quickly turned his attention toward art. Wordsworth says of him, “While yet a child, and long before his time, had he perceived the presence and the power of greatness.”
Citation: Bailey, Effie Elizabeth. John Ruskin : his life and works. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: John Ruskin; Literature; Art; Ethics; Sociology; Theses; Manuscripts (documents)